The Influence of Environmental Awareness, Consumption Values, and Price Perception on the Purchase Intention of Avoskin Green Skincare - Nuraeni, Pitri; Harsoyo, Titik Desi (East Asian Journal of Multidisciplinary Research, 2024)
This study examines the influence of environmental awareness, consumption values, and price perception on the purchase intention of Avoskin green skincare products. The sample consists of 100 respondents who are followers of the Rubi Community on Instagram and have never purchased Avoskin products. Data was collected through a survey using a questionnaire. The research instrument was proven valid and reliable, and the data was normally distributed without issues of multicollinearity and heteroscedasticity. The results indicate that environmental awareness, consumption values, and price perception each have a positive and significant influence on the purchase intention of Avoskin green skincare products.